PENGARUH KUALITAS TIDUR TERHADAP HASIL BELAJAR MATA KULIAH STATISTIKA MAHASISWA SEMESTER 1 PENDIDIKAN FISIKA UNIVERSITAS NEGERI YOGYAKARTA - Ramadani, Annisa Rizka Nur (Asosiasi Dosen Muda Indonesia, 2023)
Changes in sleep patterns depend on daily activities or activities. Activities that are too busy will have an impact on reducing a person's sleep duration. If this happens continuously it will affect health. Poor sleeping habits with long sleep duration will have a negative impact. Likewise, short sleep duration will also have a bad impact on the body. Sleep quality is one of the many factors that influence student learning outcomes. Sleep quality can be influenced by how fast or how long we sleep, sleep duration can be influenced by many factors such as; age, gender, genetics and health conditions can influence how much sleep a person needs. This study aims to identify the effect of sleep duration of first semester Physics Education students on their statistics learning outcomes. By knowing their study results and their sleep duration, it is hoped that students will be able to better manage their sleep hours. The method used in this research is a quantitative method which is a type of quantitative research. Data analysis using the Spearman's rho correlation statistical test, obtained a value of p = 0.153 (p > 0.05) with a confidence level of 95% so it can be concluded that there is not sufficient evidence to support the existence of a correlation between sleep quality results and learning outcomes. Students with poor sleep quality do not always have poor learning results.